The effect of the ankle syndesmosis reduction quality on the short-term functional outcome following ankle fractures - Kaftandziev, Igor; Bakota, Bore; Trpeski, Simon; Arsovski, Oliver; Spasov, Marko; Cretnik, Andrej (Elsevier BV, 2021)
A few radiographic techniques have been proposed to evaluate ankle syndesmosis reduction. The purpose of this study was to analyze post-operatively with CT-scanning the quality of ankle syndesmotic reduction. Moreover, to assess the impact of quality of syndesmotic reduction to functional outcome.